Evaluation of energy metabolism and calcium homeostasis in cells affected by Shwachman-Diamond syndrome. - Ravera, Silvia; Dufour, Carlo; Cesaro, Simone; Bottega, Roberta; Faleschini, Michela; Cuccarolo, Paola; Corsolini, Fabio; Usai, Cesare; Columbaro, Marta; Cipolli, Marco; Savoia, Anna; Degan, Paolo; et al. (Sci Rep, 2016)
Isomorphic mutation of the SBDS gene causes Shwachman-Diamond syndrome (SDS). SDS is a rare genetic bone marrow failure and cancer predisposition syndrome. SDS cells have ribosome biogenesis and their protein synthesis altered, which are two high-energy consuming cellular processes. The reported changes in reactive oxygen species production, endoplasmic reticulum stress response and reduced mitochondrial functionality suggest an energy production defect in SDS cells. In our work, we have demonstrated that SDS cells display a Complex IV activity impairment, which causes an oxidative phosphorylation metabolism defect, with a consequent decrease in ATP production. These data were confirmed by an increased glycolytic rate, which compensated for the energetic stress. Moreover, the signalling pathways involved in glycolysis activation also appeared more activated; i.e. we reported AMP-activated protein kinase hyper-phosphorylation. Notably, we also observed an increase in a mammalian target of rapamycin phosphorylation and high intracellular calcium concentration levels ([Ca(2+)]i), which probably represent new biochemical equilibrium modulation in SDS cells. Finally, the SDS cell response to leucine (Leu) was investigated, suggesting its possible use as a therapeutic adjuvant to be tested in clinical trials.